Inside Cover: Electronic Structure Changes of an Aromatic Amine Photoacid along the Förster Cycle (Angew. Chem. Int. Ed. 27/2022). Issue 27 (13th May 2022) - Eckert, Sebastian; Winghart, Marc‐Oliver; Kleine, Carlo; Banerjee, Ambar; Ekimova, Maria; Ludwig, Jan; Harich, Jessica; Fondell, Mattis; Mitzner, Rolf; Pines, Ehud; Huse, Nils; Wernet, Philippe; et al.
Abstract : Photoacids have been understood, since the pioneering work of Theodor Förster more than seven decades ago, to show a pronounced increase in acidity when electronically excited, but the underlying microscopic mechanisms have remained elusive. Sebastian Eckert et al. show in their Research Article (e202200709 ) how time‐resolved nitrogen K‐edge spectroscopy along the Förster cycle of a photoacid provides key insight into the electronic structural factors responsible for the photoacidity phenomenon.